KINERJA PELAYANAN ADMINISTRASI KEPENDUDUKAN DI UPTD KEPENDUDUKAN DAN PENCATATAN SIPIL WILAYAH IV PALABUHANRATU KABUPATEN SUKABUMI - Yulianti (STISIP Widyapuri Mandiri Sukabumi, 2022)
Population administration is a series of structuring and controlling activities in the issuance of population documents and data through population registration, civil registration, management of population administration information and the utilization of the results for public services and other sector development. UPTD Population and Civil Registration is an institution that is responsible for providing technical services for population administration in its working area. The quality of population administration services at UTPD Dukcapil Region IV Palabuhanratu is a reflection of organizational performance and the success of bureaucratic reform. The results of the analysis of the performance of population administration services of UTPD Dukcapil Region IV Palabuhanratu concluded that: (1) The aspect of employee responsiveness is quite good, although there are still employees who are slow in responding to public complaints, (2) The aspect of employee responsibility is quite good, although there are still employees who negligent in carrying out services, and (3) The aspect of employee accountability is quite good, although there are still employees who in performing population administration services do not comply with process accountability.